Plasmodium 6-Cysteine Proteins: Functional Diversity, Transmission-Blocking Antibodies and Structural Scaffolds - Lyons, Frankie M. T.; Gabriela, Mikha; Tham, Wai-Hong; Dietrich, Melanie H. (Frontiers in Cellular and Infection Microbiology, 2022)
The 6-cysteine protein family is one of the most abundant surface antigens that are expressed throughout the Plasmodium falciparum life cycle. Many members of the 6-cysteine family have critical roles in parasite development across the life cycle in parasite transmission, evasion of the host immune response and host cell invasion. The common feature of the family is the 6-cysteine domain, also referred to as s48/45 domain, which is conserved across Aconoidasida. This review summarizes the current approaches for recombinant expression for 6-cysteine proteins, monoclonal antibodies against 6-cysteine proteins that block transmission and the growing collection of crystal structures that provide insights into the functional domains of this protein family.